FAMILY COMMUNICATION AND PROBLEM SOLVING FOR MUSLIM TEENAGERS - Noonart, Tassanee; Lahukarn, Benjawan; Muksing, Witchuta (Journal of MCU Nakhondhat, 2020)
This academic article aims to see the importance of family communication. The target is a Muslim teenager who is considered one of the important population groups of the nation and have to solve problems together. Muslims to be a society with a culture that is different from the Thai Buddhist society. They have traditional way of life. Some Muslims still have an attitude that blocks sex. Therefore, as a guideline to solve the problem of Muslim adolescents Effective communication between parents and teenagers is of paramount importance. Parents are an important channel to help support and solve problems that may occur to youth. Drugs and other problems concerning teenagers' sex education were the most serious problems for which parents were deeply worried. Solutions should start at home. Parents construct a loving, warm, and understanding family, take care of their children including friends of their children, and cooperate with school, community, and society to solve problems. Parents sought information about sex education from TV sex education programs, consult with peers, doctor/expert, and read sex education text.The appropriate and persuasive teaching/communication personnels were parents/close elatives/teachers/doctors/experts. The desired and required teaching subject matters were sex education in general covering the early teen to young adult.